1993
DOI: 10.1111/j.1365-2133.1993.tb00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Barrier function parameters in various keratinization disorders: transepidermal water loss and vascular response to hexyl nicotinate

Abstract: In this study, we characterized the stratum corneum barrier function in 39 patients with various keratinization disorders (autosomal dominant ichthyosis vulgaris [ADI] [n = 7], X-linked recessive ichthyosis [XRI] [n = 6], autosomal recessive congenital ichthyosis [CI] [n = 10], dyskeratosis follicularis [Darier's disease; DD] [n = 8], erythrokeratoderma variabilis [EKV] [n = 8]), and 21 healthy volunteers, using two non-invasive methods: transepidermal water loss (TEWL) measuring outward transport of water thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
53
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 13 publications
8
53
0
Order By: Relevance
“…However, the functional differences between patients and controls were small (Figure 2). This is in concordance with earlier reports in human subjects 41,45 and with data from animal models. 26 -29 In the latter, permeability was increased for exogenous chemicals such as allergens despite functional differences being small.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the functional differences between patients and controls were small (Figure 2). This is in concordance with earlier reports in human subjects 41,45 and with data from animal models. 26 -29 In the latter, permeability was increased for exogenous chemicals such as allergens despite functional differences being small.…”
Section: Discussionsupporting
confidence: 94%
“…36 Since FLG peptides normally associate with both the CE [37][38][39] and keratin filaments, 40 FLG deficiency could compromise permeability barrier function by either mechanism, by both mechanisms, or by a mechanism that is unique to IV. Although in the pre-genotype era, barrier function was shown to be moderately abnormal in IV and AD patients, [41][42][43][44][45] this has not been assessed in genotyped, FLG-deficient IV patients, and there is little evidence for the mechanisms of a potential barrier defect. Therefore, we asked here whether FLG deficiency provokes allele-, and dose-dependent changes in epidermal function, and set out to clarify the subcellular basis for such abnormalities.…”
mentioning
confidence: 99%
“…In accordance, mice heterozygous for a truncated keratin K10, as a model for the ichthyosis called epidermolytic hyperkeratosis, which is caused by point mutations in the suprabasal K1 or K10 (Cheng et al, 1992;Chipev et al, 1992;Rothnagel et al, 1992;Yang et al, 1997;Suga et al, 1998;Ishida-Yamamoto et al, 2000), did not show K6/K16 protein expression in flank skin (Porter et al, 1998). Ichthyosis is a group of skin disorders with different causes, showing disturbed epidermal differentiation with variable effects on the permeability barrier (Lavrijsen et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Frost et al 14 reported a 1.2-to 1.4-fold increase in TEWL level in a cohort of patients with ichthyosis. Lavrijsen et al 15 analyzed the water barrier function in different types of keratinization disorders and showed that an elevated TEWL level discriminates differences in skin function between most patients with ichthyosis and normal volunteers.…”
Section: Commentmentioning
confidence: 99%
“…[15][16][17] In most of these studies, including our own, TEWL was measured solely at baseline. Even in situations where TEWL levels are normal or near normal at baseline, an underlying defect often becomes apparent after the presence of stress, as in aging, 18 psychological stress, 19 enviromental stress, 20 and in X-linked recessiveichthyosis.…”
Section: Commentmentioning
confidence: 99%